Analisis Penerapan Model UTAUT 2 Behavioral Intention dan Use Behavior Penggunaan Aplikasi Pedulilindungi - Fauziah, Amelisa; Juwita Ermawati, Wita; Hidayati, Nurul (IPB University, 2024)
The increase in COVID-19 positive cases in Jakarta Province in 2022, namely 1,112,007 positive cases of COVID-19 and among them 14,239 of them died, has become an alarm for the Indonesian government to immediately take effective countermeasures. This is because Jakarta is the largest government and economic center in Indonesia. One of the efforts made is by enforcing the Restriction of Community Activities (PPKM). This PPKM aims to limit community mobility in various sectors in order to minimize the chain of spread of COVID-19 cases in Indonesia. The implementation of Community Activity Restrictions (PPKM) has led to restrictions on community movement across various sectors. To monitor this mobilization, the government introduced the PeduliLindungi digital platform in April 2020 as part of its ongoing strategy to manage the COVID-19 pandemic. This study aimed to evaluate the acceptance and usage of the PeduliLindungi app using the UTAUT2 model. Conducted in 2022, the research employed purposive sampling with 256 respondents. Descriptive analysis and Structural Equation Modeling (SEM) – PLS were used for data analysis. The findings reveal that four UTAUT2 factors—performance expectancy, facilitating conditions, price value, and habit—impact Behavioral Intention. Specifically, higher levels of satisfaction and habitual use of PeduliLindungi strengthen the intention to use the app. Facilitating conditions, habit, and Behavioral Intention also influence actual usage behavior: better facilitating conditions correlate with more frequent use of PeduliLindungi. Additionally, the study found that variables such as age, gender, and internet experience did not significantly affect Behavioral Intention or usage behavior.